WO3/p-type-GR layered materials for promoted photocatalytic antibiotic degradation and device for mechanism insight - Zhao, Wenfeng (2019)
Graphene enhanced WO3 has recently become a promising material for various applications. The understanding of the transfer of charge carriers during the photocatalytic processes remains unclear because of their complexity. In this study, the characteristics of the deposited WO3/graphene layered materials were investigated by Raman spectroscopy, UV–vis spectroscopy, and SEM. According to the results, p-graphene exhibits and enhances the characteristics of the WO3/graphene film. The photocatalytic activities of WO3/graphene layered materials were assessed by the photocatalytic degradation of oxytetracycline antibiotics as irradiated by UV light. Here, a higher current of cyclic voltammetry and a higher resistance of impedance spectra were obtained with the as-grown WO3/graphene directly synthesized on Cu foils under UV light using an electrochemical method, which was different from traditional WO3 catalysts. Thus, it is urgent to explore the underlying mechanism in depth. In this study, a large layered material WO3/graphene was fabricated on a Si substrate using a modified CVD method, and a WO3/graphene device was developed by depositing a gold electrode material and compared with a WO3 device. Due to photo-induced doping effects, the current-voltage test suggested that the photo-resistance is larger than dark-resistance, and the photo-current is less than the dark current based on WO3/graphene layered materials, which are significantly different from the characteristics of the WO3 layered material. A new pathway was developed here to analyze the transfer properties of carriers in the photocatalytic process.